Corporate innovation : case study E.ON - Dvořáčková, Anna; Tyll, Ladislav; Záklasník, Martin; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2019)
This thesis is about innovation management in company. It is about realising why innovation is important and that it needs to be given significant attention in a corporation. The analysis is based on literature review and interviews with involved companies. The findings show that management of innovation is pure in big companies. After the analysis there is set of recommendations that E.ON CZ should take into account.
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses